2023
DOI: 10.1021/acs.langmuir.2c03010
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Mediated Protein Stabilization on Nanoscopic Surfaces

Abstract: The emergence of nanoparticles in biomedical applications has made their interactions with proteins inevitable. Nanoparticles conjugated with proteins and peptide-based constructs form an integral part of nanotherapeutics and have recently shown promise in treating a myriad of diseases. The proper functioning of proteins is critical to achieve their biological functions. However, interface issues result in the denaturation of proteins, and the loss of orientation and steric hindrance can adversely affect the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The protein aggregation propensity reduces with increasing IL concentrations over an extended 365 days of storage, even under stress conditions. The same choline chloride IL was used to determine the mechanism by which lysozyme-nanoparticle interactions are stabilized, and this system was compared with other choline dihydrogen citrate bio-IL-based systems to investigate the role of anions in the ILs (Figure 5A) [54]. Bisht et al used a series of choline-based bio-ILs to investigate the stability of the chymotrypsin structure against thermal denaturation and revealed that choline acetate IL-containing chymotrypsin shows a high stabilizing capacity among all studied ILs and choline hydroxide solution [55].…”
Section: Macromolecular Therapeutic Stabilizersmentioning
confidence: 99%
“…The protein aggregation propensity reduces with increasing IL concentrations over an extended 365 days of storage, even under stress conditions. The same choline chloride IL was used to determine the mechanism by which lysozyme-nanoparticle interactions are stabilized, and this system was compared with other choline dihydrogen citrate bio-IL-based systems to investigate the role of anions in the ILs (Figure 5A) [54]. Bisht et al used a series of choline-based bio-ILs to investigate the stability of the chymotrypsin structure against thermal denaturation and revealed that choline acetate IL-containing chymotrypsin shows a high stabilizing capacity among all studied ILs and choline hydroxide solution [55].…”
Section: Macromolecular Therapeutic Stabilizersmentioning
confidence: 99%
“…39 For instance, MD simulations have been used to investigate how ion-mediated interactions influence protein stabilization on nanoparticle surfaces. 40 Dai et al used MD simulations to investigate ion-mediated attractive interactions between DNA molecules and rationalized this attractive force through the formation of ion bridges. 41 Lewis et al…”
Section: Introductionmentioning
confidence: 99%
“…36 However, the attachment of the protein to the nanoparticle surface is critical for obtaining exquisite biochemical information, specifically from the surface of the protein, as the SERS enhancement diminishes exponentially from the surface of the plasmonic nanoparticles. 37 The electrons generated due to pre-irradiation also aid in this regard, as they help enhance the attachment of the protein molecules to the surface of the nanoparticles. For the first time, we demonstrate this alternate method of improving the surface attachment of proteins by activating cystine thiol groups similar to that employed in light assisted molecular immobilization (LAMI).…”
Section: Introductionmentioning
confidence: 99%